Towards a critical literature on work, family and community in resource dependent rural Australia - Mayes, Robyn; Pini, Barbara (incomplete, 2009)
The ‘resource boom’ that occurred in Australia over the past decade and the more recent detrimental impact of the global financial crisis on the resource sector nationally have elicited significant media attention, but far more limited scholarly commentary. At the same time this literature has been somewhat partial as scholarship has primarilyfocused on the workplace as the key (or only) site of analysis and thus left the relationship between mining work and families and communities under theorized. This paper makes a contribution to addressing this gap through a case study of the closure of the Ravensthorpe nickel mine in the south-west of Western Australia in January 2009. While participants in the research described many of the features of contemporary mining work that have been well documented in the literature such as the use of contract and fly-in/fly-out labour, they drew attention to the connections between these shifting work practices and family and community relations. In conclusion, the authors identify critical future research directions.